The effects of q and cash flow on investment in the presence of measurement error - Abel, Andrew B. (Journal of Financial Economics, 2018)
I analyze investment, q, and cash flow in a tractable stochastic model in which marginal q and average q are identically equal. I introduce classical measurement error and derive closed-form expressions for the coefficients in regressions of investment on q and cash flow. The cash-flow coefficient is positive and larger for faster growing firms, yet there are no financial frictions in the model. I develop the concepts of bivariate attenuation and weight shifting to interpret the estimated coefficients on q and cash flow in the presence of measurement error.